2007
DOI: 10.1002/bit.21531
|View full text |Cite
|
Sign up to set email alerts
|

Study of pellet formation of filamentous fungi Rhizopus oryzae using a multiple logistic regression model

Abstract: Fungal pellet formation is an important topic of fermentation research. It has been reported that many factors such as agitation, medium nutrients, pH, polymer additives, and inoculum size influence the formation of fungal pellets. However, a few studies on the effects of all of these factors on fungal pellet formation have been reported. This paper conducted a comprehensive investigation using a completely randomized design (CRD) on a filamentous fungus, Rhizopus oryzae NRRL 395, in order to discover the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Fungal self-pelletization has been observed for numerous filamentous strains and can be explained by coagulative and non-coagulative mechanisms [37], [38], [39], [15], [40]. The coagulative mechanism observed in representatives of Aspergillus spp , Basidiomycete spp , Phanerochaete spp involves spore coagulation leading to developments of aggregates/pellets.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal self-pelletization has been observed for numerous filamentous strains and can be explained by coagulative and non-coagulative mechanisms [37], [38], [39], [15], [40]. The coagulative mechanism observed in representatives of Aspergillus spp , Basidiomycete spp , Phanerochaete spp involves spore coagulation leading to developments of aggregates/pellets.…”
Section: Introductionmentioning
confidence: 99%
“…Fumaric acid production decreased significantly with increased ethanol production when oxygen is limited [6]. Extensive research has thus focused on how to control the fungal morphology and physiology (metabolism) for fumaric acid biosynthesis [7][8][9][10][11][12]. During submerged fermentation, filamentous fungi can grow into various morphologies, including free mycelia with hyphae dispersed in the fermentation broth, smooth and hairy pellets with a discernible core of highly entangled networks of hyphae, small loose mycelial clumps, and large densely aggregated mycelia [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that many factors such as agitation, medium nutrients, pH, polymer additives, and inoculum size influence the formation of fungal pellets. However, a few studies on the effects of all of these factors on fungal pellet formation have been reported [15]. This paper conducted a comprehensive investigation on various factors effecting dimorphism in a filamentous fungus, R. oryzae PR7 with a normal filament-pellet cycle of 90 days and a potential producer of several extra cellular cellulolytic, amylolytic and other enzymes.…”
Section: Introductionmentioning
confidence: 99%